Biological activities from andiroba (Carapa guianensis Aublet.) and its biotechnological applications: A systematic review - Dias, Kaio Kelvin Barros; Cardoso, Adauto Lima [UNESP]; da Costa, Ana Alice Farias; Passos, Marcele Fonseca; Costa, Carlos Emmerson Ferreira da; Rocha Filho, Geraldo Narciso da; Andrade, Eloísa Helena de Aguiar; Luque, Rafael; Nascimento, Luís Adriano Santos do; Noronha, Renata Coelho Rodrigues (My University, 2023)
Carapa guianensis is a tree from Meliaceae family traditionally known as andiroba that has a wide range of biological properties, including therapeutic effects, antioxidant activities, insecticidal and repellent effects that can be used in biotechnological approaches to medicine, agriculture, and cosmetic products. Therefore, we aim to explore the biological activities exhibited by this species and their respective biotechnological applications of interest. For this, a systematic review was carried out following the PRISMA guidelines dated from 1993 to 2022 through the Scopus, Web of Science and Agricultural Research Database (Base de Dados da Pesquisa Agropecuária - BDPA), screened for biological activity/bioactive compounds. A total of 129 studies were included in the PRISMA flow analysis. Biological properties and major bioactive compounds, as well as biotechnological approaches could be identified. The biological activity from C. guianensis could be observed in different vegetative parts through diverse methods of extractions. These activities are mainly due to the unsaturated fatty acids and bioactive compounds, such as the limonoids and a small fraction of phenolic compounds. Gedunin-type limonoids, like gedunin and its derivatives, represent the class of compounds that show the highest bioactivities in different applications.
Keywords: Bioactive compounds; Biological properties; Biomedical potential; Fatty acids; Gedunin; Limonoids